Permainan Kata Berpasangan Efektif Meningkatkan Keterampilan Menulis Bahasa Indonesia Kelas X SMA Negeri 9 Tangerang - Midras, Vedia (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
The use of di and ke both as prefixes or prepositions in Indonesian is unavoidable. However, students often make mistakes when writing them. The lack of understanding of the difference in writing between prefixes and prepositions is the reason for this. The use of the paired word game method aims to improve students' writing skills. This research is a class action research. CAR includes four phases, namely planning, action, evaluation and reflection. CAR is carried out using two cycles. The results of research on students' abilities in learning to write text Observation Reports of class SMA Negeri 9 Tangerang have increased. The results of the evaluation of the first cycle when using paired word games showed an increase in category A (86-100) 27%, category B (75-85) 6%. The results of the evaluation of the second cycle increased even more so that category A increased to 61%, and category B increased to 39%. There were no more students with grades in categories C, D, and E. Thus it can be said that all students succeeded in achieving scores of more than 75. From the implementation of the 2 cycles, it can be concluded that learning using word games in pairs can improve students' writing skills.